Late Neanderthal subsistence and foraging mobility at Lapa do Picareiro: a zooarchaeological and taphonomic analysis of Level JJ - Carvalho, Milena; Haws, Jonathan A.; Jones, Emily Lena (Frontiers in Environmental Archaeology, 2025)
Recent revisions of Neanderthal behavioral models call into question the notion of inflexible subsistence strategies. Here, we present new zooarchaeological and taphonomic data from Level JJ at Lapa do Picareiro (Portuguese Estremadura), dating to ~51.5–42.5 ka cal BP, to evaluate Neanderthal prey selection, mobility, and adaptive responses to climatic fluctuations during MIS 3. Our zooarchaeological and taphonomic analysis of macro-mammalian faunal assemblages—divided into three stratigraphic subunits—reveals a consistent emphasis on red deer exploitation, supplemented by occasional hunting of ibex, chamois, aurochs, and horse. Despite paleoenvironmental disturbances associated with Heinrich Stadial (HS) 5, the stable abundance and processing of red deer indicate that these key resources remained reliable, supporting a localized foraging territory estimated at 225–400 km2. In contrast, the lithic record shows a shift in raw material procurement before and after the climatic event, suggesting adaptive technological responses. Overall, our findings imply that Neanderthals at Picareiro employed brief, intermittent site occupations while maintaining resilient, regionally adapted subsistence and mobility strategies in the face of environmental variability.